Effects of calorie labelling and contextual factors on hypothetical coffee shop menu choices. (1st May 2022) - Tapper, Katy; Yarrow, Kielan; Farrar, Stephanie T.; Mandeville, Kate L.
Abstract: This study examined the effects of calorie labelling and two key contextual factors (reflective motivation and habits) on the calorie content of hypothetical coffee-shop menu choices. In one exploratory ( n  = 70) and one pre-registered ( n  = 300) laboratory study (Studies 1 and 2 respectively), participants viewed a hypothetical calorie-labelled or non calorie-labelled menuboard and selected their preferred item(s). Coffee shop drinking habits were measured using the Self-Report Habit Index, and reflective motivation (relating to calorie intake) was assessed with three items asking about watching weight, eating healthily, and reading calorie labels. In Study 2, participants also estimated calories contained in a subset of the menuboard drinks. Results of both studies showed that labelling did not significantly affect the total calorie content of items selected. However, in Study 2, as predicted, there was a trend toward moderation by reflective motivation ( p  = .056) with less motivated participants showing relatively greater calorie selection when exposed to labelling. Participants with weaker habits took longer to select items ( p  = .002) but, contrary to predictions, were not more influenced by labelling. Higher reflective motivation was associated with selecting fewer calories ( p  = .002), correctly recalling the presence/absence of labelling ( p  = .016) and better estimating calorie content ( p  < .001). Overall, participants significantly underestimated calories in higher calorie drinks but overestimated calories in lower calorie drinks. The results highlight the importance of contextual factors such as habits and reflective motivation for obesity interventions and are relevant for the UK's introduction of selective mandatory calorie labelling. In some instances, labelling may actually increase intake among those less motivated by health and weight concerns, but further research is needed to substantiate this concern.